Predictors of Depression and Anxiety Symptoms in Teachers from 19 Latin American Countries and Spain Due to the COVID-19 Pandemic - Sofia Catalina Arango-Lasprilla; Natalia Albaladejo-Blázquez; Bryan R. Christ; Oswaldo A. Moreno; Juan Carlos Restrepo Botero; Paul B. Perrin; Rosario Ferrer-Cascales (Psychology International, 2025)
Background: The Coronavirus disease (COVID-19) pandemic profoundly impacted education, causing uncertainty and constant changes for teachers, including new teaching modalities, increased workloads, and limited rest periods. Global studies have reported mental health issues such as anxiety and depression among educators during and after the pandemic, primarily in Asia, Europe, and North America. However, these existing studies often show increased anxiety and depression rather than considering school-based predictors that may contribute to increasing rates. Aims: Despite these global findings, there are few investigations of the impact of COVID-19 on teachers in Latin America and Spain. To address these notable global and regional research gaps, this study examined the prevalence and predictors of depression and anxiety symptoms among teachers in Latin America and Spain. Method: An online survey collected data on demographics, work-related characteristics, COVID-19 experiences, and measures of mental health from teachers in 19 Latin American countries and Spain using a snowball sampling approach. The sample comprised 2004 teachers, with 81.8% female participants and a mean age of 44.46 years (SD = 9.8). Descriptive statistics and hierarchical multiple linear regressions were conducted with depression and anxiety as outcome variables. Results: Consistent predictors of increased anxiety and depression symptomology included being female or transgender, being younger, having lower socioeconomic status, having pre-existing mental health conditions or chronic illness, having increased workload during the pandemic, being dissatisfied with teaching resources, and having negative changes in relationships with students, parents, or colleagues. The predictors collectively explained 16.4% of the variance in depression and 17.5% of the variance in anxiety symptoms. Conclusions: The significant mental health needs of teachers in Latin America and Spain during the COVID-19 pandemic highlight the pressing necessity of prioritizing the mental health needs of educators to improve their psychological health and children’s educational environments. These results also suggest the practical need to provide teachers with additional school-based supports and resources for future transitions to online learning or disruptions to traditional instruction.